2017
DOI: 10.1093/mnras/stx2302
|View full text |Cite
|
Sign up to set email alerts
|

Improving time-delay cosmography with spatially resolved kinematics

Abstract: Strongly gravitational lensed quasars can be used to measure the so-called time-delay distance D ∆t , and thus the Hubble constant H 0 and other cosmological parameters. Stellar kinematics of the deflector galaxy play an essential role in this measurement by: (i) helping break the mass-sheet degeneracy; (ii) determining in principle the angular diameter distance D d to the deflector and thus further improving the cosmological constraints. In this paper we simulate observations of lensed quasars with integral f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 70 publications
3
94
0
Order By: Relevance
“…Joseph et al 2014;Agnello 2017;Petrillo et al 2017;Ostrovski et al 2017;Lanusse et al 2018;Spiniello et al 2018;Treu et al 2018;Avestruz et al 2019), and more are expected to be found with the Large Synoptic Survey Telescope (Oguri & Marshall 2010). Hence, a 1% H 0 measurement from time-delay cosmography is a realistic expectation in the near future (e.g., Jee et al 2015Jee et al , 2016de Grijs et al 2017;Suyu et al 2018;Shajib et al 2018, Jee et al 2019 if we can control the systematic effects to a sub-percent level (Dobler et al 2013;Liao et al 2015;Ding et al 2018).…”
Section: Distance Measurement From Time-delay Cosmographymentioning
confidence: 99%
“…Joseph et al 2014;Agnello 2017;Petrillo et al 2017;Ostrovski et al 2017;Lanusse et al 2018;Spiniello et al 2018;Treu et al 2018;Avestruz et al 2019), and more are expected to be found with the Large Synoptic Survey Telescope (Oguri & Marshall 2010). Hence, a 1% H 0 measurement from time-delay cosmography is a realistic expectation in the near future (e.g., Jee et al 2015Jee et al , 2016de Grijs et al 2017;Suyu et al 2018;Shajib et al 2018, Jee et al 2019 if we can control the systematic effects to a sub-percent level (Dobler et al 2013;Liao et al 2015;Ding et al 2018).…”
Section: Distance Measurement From Time-delay Cosmographymentioning
confidence: 99%
“…The main source of uncertainty is from the adequacy of lens models, and the role of additional mass along the line of sight (Schneider & Sluse 2013). When the velocity dispersion σ of the deflector is measured, the ratio c 3 ∆t/σ 2 ∝ D l makes these systems standard rulers independent of any cosmological model (Paraficz & Hjorth 2009), provided the degeneracies in lensing and dynamical models are suitably explored (Jee et al 2016;Shajib et al 2018), regardless of weak lensing by additional line-of-sight perturbers.…”
Section: Time-delay Lensingmentioning
confidence: 99%
“…In order to reduce systematics from the massanisotropy degeneracy, spatially-resolved kinematic measurements are needed. This has been shown to produce percent-level accuracy with realistic error budgets (Shajib et al 2018).…”
Section: Time-delay Lensingmentioning
confidence: 99%
“…1.1, with stellar kinematic and time-delay data, we can infer the angular diameter distance to the lens, D d , in addition to D t (Paraficz and Hjorth 2009;Jee et al 2015;Birrer et al 2015b;Shajib et al 2017). Measurement of D d is often more sensitive to the dark energy parameters (for typical lens redshifts 1, see e.g., Fig.…”
Section: Lens Mass Modelingmentioning
confidence: 99%
“…comm.). We therefore advocate getting exquisite follow-up observations of a sample of ∼ 40 lenses to reach an H 0 measurement with 1% uncertainty (Jee et al 2016;Shajib et al 2017), with the other lenses providing information on the profiles of galaxies to use in the mass modeling.…”
Section: Lens Mass Modelingmentioning
confidence: 99%